Influence of COO publicly and privately consumed luxury and necessity products - Goh, Kiah Kiah (2008)
This study examines the influence of Country of Origin (COO) on four various product classes, namely, Publicly Consumed Luxury (PUL), Privately Consumed Luxury (PRL),Publicly Consumed Necessity (PUN), and Privately Consumed Necessity (PRN). Over 300 people participated in a structured questionnaire in which they ranked and rated theimportance of the various product classes’ attributes (inclusive of COO as an attribute).